2022
DOI: 10.1007/s40801-021-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Persistence with Once-Daily vs Twice-Daily Direct Oral Anticoagulants Among Patients with Atrial Fibrillation: Real-World Analyses from the Netherlands, Italy and Germany

Abstract: Background Direct oral anticoagulants are available for patients with atrial fibrillation. Objective This study compared adherence and persistence of once-daily (QD) vs twice-daily (BID) direct oral anticoagulants in patients with atrial fibrillation. Methods A cohort study was conducted in three databases in the Netherlands, Italy and Germany. Patients with AF starting direct oral anticoagulants after drug approval date were included. The index date was the date of first dispensing. Study patients were restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Several previous studies have shown that NOAC adherence requiring twice-daily dosing was lower than that of once-daily dosing [ 8 , 10 ]. However, some studies individualizing each NOAC showed that the adherence to apixaban was similar to that of rivaroxaban, whereas dabigatran had lower adherence than apixaban or rivaroxaban [ 7 , 11 ], although both apixaban and dabigatran require twice-daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that NOAC adherence requiring twice-daily dosing was lower than that of once-daily dosing [ 8 , 10 ]. However, some studies individualizing each NOAC showed that the adherence to apixaban was similar to that of rivaroxaban, whereas dabigatran had lower adherence than apixaban or rivaroxaban [ 7 , 11 ], although both apixaban and dabigatran require twice-daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…In InGef and PHARMO, in case of an interruption between DOAC dispensings, use of DOACs was considered uninterrupted if the duration of this gap was less than half the duration of the preceding dispensing with a minimum of 7 days [ 20 ]. In ARS, use of DOACs was considered uninterrupted if the duration of the gap was 90 days or less, as in a previous study it was concluded that this method best fitted the ARS data [ 21 ]. Patients could have several treatment episodes after CED.…”
Section: Methodsmentioning
confidence: 99%
“…a large number of daily doses) might negatively influence adherence [15]. The once-daily dosing regimen was associated with better adherence as opposed to twice-daily in patients with atrial fibrillation receiving oral anticoagulants [33]. Adherence was decreased in patients taking many medications to treat their comorbidities, contributing to the forgetfulness of taking medications [4].…”
Section: Social Supportmentioning
confidence: 99%